2009
DOI: 10.1177/1077558708330428
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Health Care Access

Abstract: A growing interest in community-level characteristics such as social capital and their relationship to healthcare access is evident. To assess the rigor with which this construct has been empirically applied in research on healthcare access, we conducted a systematic review. A total of 2396 abstracts were reviewed, with 21 ultimately meeting our criteria of examining some measure of social capital and its effects on healthcare access. Our review found a lack of congruence in how social capital was measured and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(104 citation statements)
references
References 79 publications
2
102
0
Order By: Relevance
“…If different components of social capital are used in a single measure, then it is difficult to assess what specific factors are influencing health outcomes (Carpiano, 2006). In a review of the association between social capital and access to health care, Derose and Varda (2009) found that studies reported a differential effect of various forms of social capital on health service use, which calls into question the practice of combining these different types of variables (i.e., cognitive and structural or bonding and bridging) into summary social capital scales. Moreover, studies that distinguish between various components of social capital rarely validate the measures used, making it difficult to determine which components of social capital are actually being measured.…”
Section: Introductionmentioning
confidence: 99%
“…If different components of social capital are used in a single measure, then it is difficult to assess what specific factors are influencing health outcomes (Carpiano, 2006). In a review of the association between social capital and access to health care, Derose and Varda (2009) found that studies reported a differential effect of various forms of social capital on health service use, which calls into question the practice of combining these different types of variables (i.e., cognitive and structural or bonding and bridging) into summary social capital scales. Moreover, studies that distinguish between various components of social capital rarely validate the measures used, making it difficult to determine which components of social capital are actually being measured.…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, individuals belonging to groups possessing a greater amount of social capital are expected to exhibit lower disease rates. 2 Social capital has been examined in relation to a variety of health-related outcomes, including mortality, 8 health status, 9 sexually transmitted diseases, 10,11 mental health, 12-15 health care access, 16 and health behaviors. 17,18 Findings from studies examining social capital as a contributor to racial disparities have been inconclusive.…”
mentioning
confidence: 99%
“…Harpham, Grant, and Thomas (2002) argued that surveys lacking a connection to existing theory do not comprehensively measure social capital pointing to a deficit in available instruments. Similarly, Derose and Varda (2009) noted that many items in existing scales generalized responses rather than focusing on specific types of relationships linked to bonding (personal network relationships) and bridging (social/ organizational network relationships) aspects of social capital theory. This study made a concerted effort to provide additional evidence for the PSCS-E to improve the availability of social capital instruments derived from theory and test the validity, factor structure, and reliability of the scale.…”
Section: Discussionmentioning
confidence: 99%